Learning Local Wisdom for Character Education: an Insight from Choblong Sundanese Village in Indonesia - Miranti, Ira; Nurjanah, Nurjanah; Dwiastuty, Nina (SCAD Independent, 2018)
The purpose of this study is to describe the various local wisdom and describe the diverse character education, which contain in local wisdom in the Sundanese society of Choblong, Cisarua village located in Bogor, West Java, Indonesia. Observation method is the best way to collect information and understand local culture in a society. The local wisdom of these Choblong villagers is believed to have a useful contribution to the values of character education that must always be taught and preserved for the benefit of subsequent regeneration. The local wisdom of the Choblong village can be penetrated to school curriculum for preparing their next generations and the cultural preservation. Although there are many adjustments required when immersion between local culture and school curriculum, but it is possible if the applications of carefully selected local culture are given in their local environmental settings.